Indonesia's Value Added Tax (VAT) Reform: Fiscal Benefits and Sectoral Impacts - Muchamad Irham Fathoni (Jurnal Syntax Admiration, 2025)
This study comprehensively analyzes the impact and implications of the planned increase in Value Added Tax (VAT) rates from 11% to 12% in the wider context of the Indonesian economy. Using an analytical-descriptive approach with a literature review method, this study examines various dimensions of policy impacts, including fiscal, macroeconomic, sectoral, and implementation feasibility aspects. This study found that the increase in VAT has the potential to increase state revenues by IDR 85-95 trillion per year, but also has potential consequences of inflationary pressures of 1.1-1.4% and a short-term slowdown in economic growth of 0.3-0.4%. From a sectoral perspective, MSMEs face significant pressure with a decline in margins of 2-3%, while the formal sector shows better resilience. The implementation feasibility analysis indicates that the readiness of the tax administration system has reached 85%, although there are still several challenges in the supervision aspect. This study recommends a gradual implementation approach with an increase of 0.5% per year, accompanied by strengthening social assistance programs and special incentives for MSMEs. Periodic monitoring and evaluation framework are key to ensuring the effectiveness of this policy while minimizing negative impacts on the economy. This study concluded that the success of this policy depends on the right timing of implementation, institutional readiness, and comprehensive supporting policies.